Representasi Nilai Kepedulian Sosial pada Fiksi Digital Wattpad Drama Keluarga dalam Pembelajaran - Rini Indah Sulistyowati; Enggar Dhian Pratamanti; Ganda Januarta; Linda Novasari (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Social care values ​​are moral principles that emphasize empathy, altruism, solidarity, mutual cooperation, justice, and tolerance in social life. These values ​​form the foundation for individuals to understand the feelings of others, help selflessly, cooperate, be fair, and respect differences. This study aims to describe the representation of social care values ​​in Wattpad short stories in the family drama genre, identify the most dominant values ​​and the context in which they emerge, and explain the relevance of these findings to learning and character development in students. The study used a descriptive qualitative method because it focuses on the meaning of the text, rather than quantitative measurement. Data were collected through listening and note-taking techniques by carefully and repeatedly reading the short stories to identify sections of the text that contain social care values. Data included words, phrases, sentences, dialogue, and narratives that depict character actions, conflicts, or interactions reflecting empathy, altruism, solidarity, mutual cooperation, justice, and tolerance. All quotations were recorded on a coding sheet to organize the data systematically. Data analysis was conducted using the Miles and Huberman technique, which includes data reduction, classification, and interpretation. In the reduction stage, relevant data was selected and then grouped according to social awareness value categories. Next, interpretation was conducted to explain the representation of these values ​​in the storyline and relationships between characters.